PENGARUH KOMPENSASI, JOB SATISFACTION, DAN PERCEIVED JOB ALTERNATIVE TERHADAP TURNOVER INTENTION PADA KARYAWAN - Sahputra, Rananda; Dihan, Fereshti Nurdiana (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is to determine the influence of compensation, job satisfaction, and perceived alternative jobs on employee turnover intention. Apart from that, this research also aims to determine the effect of compensation on turnover intention through job satisfaction. The sample used in this research was 50 employees. This research uses classical assumption testing & regression as data analysis techniques, which are processed using Statistical Program Social Sciences (SPSS) version 21.0. The results of the analysis carried out stated that there was a negative and significant influence between compensation on turnover intention. Compensation has a positive and significant influence on job satisfaction. Job satisfaction has a negative and significant influence on turnover intention. Perceived alternative jobs have a positive and significant influence on turnover intention and compensation has an influence on turnover intention through job satisfaction.